Global South expatriates, homesickness and adjustment approaches - Dieu Hack-Polay (Frontiers Media S.A., 2020)
Abstract Purpose The research examines homesickness in organisationally assigned expatriates from developing countries or Global South serving in Western contexts. It investigates the extent to which homesickness has personal and organisational consequences and explores the coping mechanisms used by expatriates. Design/methodology/approach This is a qualitative research built on unstructured interviews with organisationally assigned expatriates from the Global South. Findings The research found that homesickness has consequences for both expatriates and organisations. These consequences include psycho-social disorder, deterioration of physical health which damagingly affects individual well-being, work outcomes and organisational commitment. Practical implications The practical implications centre on the opportunity for policy and strategy formulation by international human resource management (HRM) within organisations to improve the mental health of Global South expatriates, thus seeding the ingredients for better performance and job satisfaction. Originality This research makes significant additions to the expatriate literature in exposing the homesickness experiences of expatriates from the Global South in advanced economies. Two main coping frameworks used by expatriates are proposed. These copying frameworks centre on positive practices and negative practices which, in turn, encapsulate five adjustment approaches. The research explains how Global South expatriates use these models in practice.